Mechanical stability and heat transfer improvement of CaO-based composite pellets for thermochemical energy storage. (29th June 2022) - Guo, Rui; Takasu, Hiroki; Funayama, Shigehiko; Shinoda, Yasunari; Tajika, Masahiko; Harada, Takuya; Kato, Yukitaka
Highlights: Non-shelled and shelled composite pellets were introduced. The morphological change was observed and discussed. The hydration/dehydration cyclic performances were compared. The crushing strength of shelled composite pellets was 49 N after 22 cycles. The output/storage density of shelled composite pellets exceeded 1000 kJ Lpellet −1 . Abstract: Two types of composite pellets of CaO (non-shelled and shelled) are examined to improve the mechanical stability and heat transfer efficiency of a CaO/H2 O/Ca(OH)2 thermochemical energy storage system. To prepare a non-shelled composite pellet, a mixture comprising calcium carbonate (CaCO3 ) and carboxymethyl cellulose (CMC) is pressed into a cylindrical shape and then calcinated. Subsequently, a shelled composite pellet is obtained by calcinating the pressed mixture of CaCO3 and CMC after embedding it into silicon carbide diesel particle filters. Analyses of the morphology variations of the non-shelled composite pellets in hydration/dehydration operations show that the change in their bulk volume is reduced significantly. CaO crystals pile up layer by layer in a rod-like shape in the pellets, thereby preventing volume expansion. The numerous micropores in the pellets enhance the gas–solid reactivity. The shelled composite pellets attain the advanced performances in mechanical stability, reactivity and output/storage density as thermochemical energy storage materials.